Anti-cyclic citrullinated peptide antibodies in systemic lupus erythematosus patients with articular involvement: a predictive marker for erosive disease? - A. Tincani; I. Cavazzana; A. Ceribelli; M. Fredi; F. Inverardi; M. Taraborelli; F. Franceschini (PAGEPress Publications, 2012)
A small number of systemic lupus erythematosus (SLE) patients develop an erosive disease. Some studies have suggested an association between anti-cyclic citrullinated (anti-CCP) antibodies and this pattern of arthritis, but their exact significance in SLE patients remains unclear. The aim of this study was to evaluate the prevalence of anti-CCP antibodies in SLE patients with different subsets of articular disease. Among 521 SLE patients followed in this center from 1976 to 2011, those with articular involvement (n=298) were selected to take part in the study. We searched for anti-CCP2 IgG antibodies in 198 patients using a commercial enzyme linked immunosorbent assay (Immunoscan RA, Eurodiagnostica). In 174 patients the results for rheumatoid factor (RF) by nephelometry were retrospectively collected. C reactive protein (CRP) was obtained from clinical records. Patients were classified into 3 groups: erosive, non-erosive deforming, non-erosive non-deforming arthritis. Results of the different tests were compared among the groups. P<0.05 was considered statistically significant. Anti-CCP antibodies were significantly associated with erosive disease. We also found that RF positivity and increased CRP were more frequent in erosive arthritis and erosive or non-deforming arthritis, respectively, than in non-erosive non-deforming arthritis. This study supports the evidence that anti-CCP antibodies could be a useful marker of erosive disease in SLE patients. Increase in RF and CRP could be an additional means of identifying lupus patients with arthritis at risk of a worse prognosis.